MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA DALAM PEMBELAJARAN BANGUN RUANG SISI DATAR MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT PADA SISWA KELAS VIII-I SMP DWIJENDRA DENPASAR TAHUN AJARAN 2011/2012 - Maheni, Ni Nyoman; Putra, I Gusti Ngurah Nila (Jurnal Santiaji Pendidikan (JSP), 2014)
This study aimed at improving the activities and achievements of students learning. This research is a Class Action Research which was done in three cycles. Based on the result of data analysis, it shows that the student learning activity score of cycle I until cycle III and category in a row are â€œ14,897â€, â€œ19,583â€, and â€œ20,710â€ with category are â€œfairly activeâ€, â€œactiveâ€, and â€œvery activeâ€. The result of data analisys of learning achivement, the average score, mastery learning, and absorptive ability of cycle I until cycle III in a row are â€œ7,67â€, â€œ7,77â€, and â€œ8,25â€; â€œ53,85%â€, â€œ71,05%â€, and â€œ89,74%â€; and â€œ76,7%â€, â€œ77,7%â€, and â€œ82,5%â€. The result of data analisys of implementation of the learning of cycle I until cycle III and category in a row are â€œ79,54%â€, â€œ93,175%â€ and â€œ100%â€ with category are â€œgoodâ€, â€œvery goodâ€, and â€œvery goodâ€. While for result analisys data of student response, achieving very positive category with an average score of responses student â€œ32,13â€. Thus, the application of cooperative learning type TGT in learning the math flat side geometry can improve the activities and achievements of students learning.